Cultural Content Analysis of English Textbook for 10th Grade: Bahasa Inggris - Lam'atut Durori (Graduate Program, University of Islam Malang, 2021)
As the fundamental sources of language learning, yet some researchers found that many English textbook did not match to the students’ need, while good English textbook does not only emphasize the language acquisition but also provide and introduce cultural meaning to the students (Tomlinson, Swain, and Kramsch in Toledo-Sandoval, 2020). The use of local culture in language material improved students’ cultural awareness and motivate them to intercultural interaction. Thus, Indonesian English language teaching material should offer them real life and contextualized communication. The local cultural values refer to the 83 values within Pancasila and daily life, and Some character of textbook brings into line with philosophy base of Permendikbud No 36 year 2018, that broke down into 29 aspect. The method was qualitative descriptive content analysis approach. The data derived from the locally produced ELT textbook of senior high school grade X, XI, XII of senior high school published by Kemendikbud by used 8 procedure to conduct the study, then crosscheck the data, discuss and consult to the expert and advisor repeatedly. From that method found out that there are 30 variety for grade X, 31 variety for grade XI, and 33 variety for grade XII of local cultural values. Some activities given engage students’ critical thinking and evolve psychomotorand affective competencies and based on nowadays situation whereas some main materials in some chapters are not contextualized. Thus, it is a necessity to build the quality of this book, by evaluate each chapter and consider the local cultural values needed on it and mentioned in curriculum.